Reduced Carboxylate Graphene Oxide based Field Effect Transistor as Pb2+ Aptamer Sensor - Fang Li; Zhongrong Wang; Yunfang Jia (Micromachines, 2019)
Aptamer functionalized graphene field effect transistor (apta-GFET) is a versatile bio-sensing platform. However, the chemical inertness of graphene is still an obstacle for its large-scale applications and commercialization. In this work, reduced carboxyl-graphene oxide (rGO-COOH) is studied as a self-activated channel material in the screen-printed apta-GFETs for the first time. Examinations are carefully executed using lead-specific-aptamer as a proof-of-concept to demonstrate its functions in accommodating aptamer bio-probes and promoting the sensing reaction. The graphene-state, few-layer nano-structure, plenty of oxygen-containing groups and enhanced LSA immobilization of the rGO-COOH channel film are evidenced by X-ray photoelectron spectroscopy, Raman spectrum, UV-visible absorbance, atomic force microscopy and scanning electron microscope. Based on these characterizations, as well as a site-binding model based on solution-gated field effect transistor (SgFET) working principle, theoretical deductions for rGO-COOH enhanced apta-GFETs’ response are provided. Furthermore, detections for disturbing ions and real samples demonstrate the rGO-COOH channeled apta-GFET has a good specificity, a limit-of-detection of 0.001 ppb, and is in agreement with the conventional inductively coupled plasma mass spectrometry method. In conclusion, the careful examinations demonstrate rGO-COOH is a promising candidate as a self-activated channel material because of its merits of being independent of linking reagents, free from polymer residue and compatible with rapidly developed print-electronic technology.